Crucial conversations : tools for talking when stakes are high - Patterson, Kerry, 1946-; Grenny, Joseph; McMillan, Ron; Switzler, Al (McGraw Hill-Ascent Audio, 2011)
Perhaps once a decade, a book comes along that transforms people's lives in a very real, measurable way. This is one of them. Crucial Conversations exploded onto the scene ten years ago and revolutionized the way people communicate when stakes are high, opinions vary, and emotions run strong. Since then, millions of people have learned how to hold effective crucial conversations and have dramatically improved their lives and careers thanks to the methods outlined in this book. Now, the authors have revised their bestselling classic to provide even more ways to help you take the lead in any tough conversation: New firsthand accounts of how these skills changed readers' lives New case studies showing how business leaders successfully applied these methods to achieve results New links to videos teaching what to do and what to avoid during crucial conversations New research findings offering fresh insights for applying the skills taught in the book Crucial Conversations is filled with practical advice you can start using today: Prepare for high-stakes conversations Make it safe to talk about almost anything Transform unpleasant emotions into powerful dialogue Be persuasive, not abrasive Crucial Conversations gets you past the hard parts of dialogue and helps you achieve relationships that are real, productive, and that will enrich your life and career.